1999
DOI: 10.1093/ejo/21.4.377
|View full text |Cite
|
Sign up to set email alerts
|

A long-term evaluation of treated Class II division 2 malocclusions: a retrospective study model analysis

Abstract: Pre-treatment, end of treatment, and post-retention study models of 30 subjects with a Class II division 2 malocclusion were assessed, after a period of at least 3 years, in order to evaluate the long-term changes in occlusion, alignment, and arch dimensions. Molar relationship correction was found to be stable after retention. There were no variables which could be used to establish a prognosis of vertical stability. Over-correction of overbite was seen to relapse. Ten per cent of the cases showed unacceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 14 publications
0
40
1
10
Order By: Relevance
“…The mean post-retention duration in this study was 15 years, with the minimum being 8.6 years. In a similar study, Canut & Arias (1999) observed a mean overbite correction of 3.5 ± 1.8 mm in 30 Class II division 2 subjects during active orthodontic treatment, which relapsed 0.9 ± 1.2 mm during the post-retention period (mean duration = 7 years). Preston, Maggard, Lampasso et al (2008) found a statistically significant, but clinically insignificant, amount of relapse after levelling the Curve of Spee (COS) in deep bite patients.…”
Section: Overbite Relapsementioning
confidence: 62%
See 2 more Smart Citations
“…The mean post-retention duration in this study was 15 years, with the minimum being 8.6 years. In a similar study, Canut & Arias (1999) observed a mean overbite correction of 3.5 ± 1.8 mm in 30 Class II division 2 subjects during active orthodontic treatment, which relapsed 0.9 ± 1.2 mm during the post-retention period (mean duration = 7 years). Preston, Maggard, Lampasso et al (2008) found a statistically significant, but clinically insignificant, amount of relapse after levelling the Curve of Spee (COS) in deep bite patients.…”
Section: Overbite Relapsementioning
confidence: 62%
“…This lower incisor collapse back to their original, more retroclined position would definitely result in a deepening of the overbite. In their retrospective study of thirty Class II division 2 subjects, Canut & Arias (1999) found a statistically significant correlation (r = 0.52, p < 0.01) between post-retention lower crowding and post-retention overbite increase, although this association was weaker than expected.…”
Section: Incisal Angulation Changesmentioning
confidence: 85%
See 1 more Smart Citation
“…1 The important considerations in orthodontic treatment of adult malocclusion include the decision regarding extraction of teeth and the improvement of a deep bite. The decision should be planned according to arch length discrepancy, stability after orthodontic treatment, and the anteroposterior position of the incisors in relation to the lips.…”
Section: Introductionmentioning
confidence: 99%
“…Outros ainda avaliam a estabilidade da Classe II associando-a a fatores com a recidiva do apinhamento ântero-inferior, do comprimento do arco, das distâncias intercaninos e intermolares, do overbite e do overjet (ÅRTUN; GAROL; LITTLE, 1996;BISHARA et al, 1994a;BUSATO, 2003;CREPALDI, 2005;SCHWARZE, 1995;SCHWARZE, 1996;NAHÁS, 2000;NASHED;REYNOLDS, 1989;SHIELDS;LITTLE;CHAPKO, 1985;SIQUEIRA et al, 1999). Há avaliações cefalométricas e em modelos, ou em ambos (BINDA et al, 1994;BISHARA et al, 1994b;BIRKELAND et al, 1997;CANUT;ARIAS, 1999;CIGER;AKSU;GERMEÇ, 2005;ALEXANDER, 1996a;ALEXANDER, 1996b;HERZBERG, 1973;KIM et al, 2000;ORMISTON et al, 2005;OTUYEMI;JONES, 1995;CRAWFORD, 2000). Outras avaliações abordam as diferenças com relação à época do tratamento, ou seja, em pacientes adolescentes e adultos (HARRIS; MCREYNOLDS;LITTLE, 1991;MIYAZAKI et al, 1998).…”
Section: Estabilidade Recidiva E Fatores Relacionadosunclassified